Redutibilidade salarial no contexto pandêmico: a constitucionalidade da redução salarial sem a participação do sindicato - Mota, Marina Ribeiro (2023)
The main goal of the present work is to analyze and define the constitutional limits to the validity of the salary reduction celebrated without prior union participation, as prescribed in Provisional Measure no 936/2020 and in the norms that were grounded on it - based on the prevailing factual circumstances in a pandemic context/context of public calamity. Although the aforementioned Measure aimed to preserve employment and income in the face of the economic crisis generated by the Covid-19 pandemic, its constitutionality has become questionable due to fact that the item VI of the 7th article of the Federal Constitution of Brazil allows the agreement of salary reduction only through collective bargaining. Thus, the specific objectives outlined were: to analyze the constitutionality of the 7th article of PM no 936/2020 (later replicated in other regulations), from the perspective that such article would not culminate in the reduction of social rights, but rather in the feasibility (in the face of a calamitous situation) of the constitutionally guaranteed possibility of wage reduction; analyze the unconstitutionality of article 7th of PM no 936/2020, from the perspective of the imperative nature of the Constitution, the importance of union participation and the insufficient protection of social rights; investigate the proper interpretation to be given to item VI of article 7th of the Federal Constitution in an emergency scenario. The research is classified as basic, explanatory, qualitative, documental and bibliographical, alternating between deductive and inductive methods of scientific approach. The methodology adopted proved to be satisfactory, and it was possible to achieve the programmed objectives. Having tested the hypotheses and carried out the analyses, it was concluded, in summary, that: constitutional norms can and should be made more flexible if their reinterpretation is necessary to materialize their essential content, since the dynamism inherent to the factual reality prevents the legislator from exhaustively foresee all possible scopes and forms of Law enforcement; the salary reduction regulated in the pandemic context/context of public calamity (PM no 936/2022 and its derived norms) is unconstitutional, not due to an attachment to the literality of the republican text, but because the regulations elaborated disproportionately distanced the unions from the process of salary reduction agreements, violating the essential content of item VI of article 7th of the Federal Constitution, in addition to item III of its article 8th; PM no 936/2020 seriously failed by not requiring proof of the unions’ inaccessibility and also by not including other mechanisms and entities to alleviate the material inequality between the parties; although a fundamental right may mitigate another (which would open the possibility of PM no 936/2020 being seen as constitutional), in the Brazilian experience, the favored fundamental right (right to employment guarantee) was preserved at the expense of other fundamental rights through a regulation that, if it had been made with greater appreciation of the unions, could have resulted in a minimally adequate guarantee of labor rights, which was not the case; any extremist interpretation of a constitutional norm (strong stiffness or extensive flexibility) will achieve the same result – the disprotection of the law’s essential core.